Growth traits of slaughter F1 lambs in northeast of Brazil - Barros, Nelson Nogueira; Vasconcelos, Vânia Rodrigues de; Lobo, Raimundo Nonato Braga (Pesquisa Agropecuaria Brasileira, 2004)
The aim of this work was to determine the influence of the ram in the growth traits of 303 slaughter lambs of ½ Somalis Brasileira x ½ Undefined Breed (SRD) and ½ Santa Inês x ½ SRD genetic groups. The animals were weighted each 14 days until weaning at dry season and up to 140 days of age at rainy season. The genetic group and the year of birth did not influence (P>0.05) any of the analyzed traits. The month of birth influenced (P<0.05) weights at birth, at 56 days of age and at weaning, and weight gain until weaning. February was the best month to birth of lambs. Single animals weighted more and gained more weight (P<0.05) than those of multiple births, in all ages and studied intervals, except in the period between weaning and the age of 140 days. Males were heavier and gained more weight than females, both in the pre-weaning and in the post-weaning period. The two analyzed genetic groups are similar as to body weight and weight gains, both in the pre-weaning and in the post-weaning period.